Atomic adventures : secret islands, forgotten N-rays, and isotopic murder - a journey into the wild world of nuclear science - Mahaffey, James A. (2017)
Mahaffey unearths lost reactors on far-flung islands and finds trees that were exposed to active fission -- which then changed gender or bloomed in the dead of winter. He explains why we have nuclear submarines but not nuclear aircraft and why cold fusion does not -- and cannot -- exist. And who knew that radiation-counting was once a fashionable trend? Though parts of our nuclear history might seem like fiction -- such as when cowboys got their hands on a reactor -- Mahaffey's prose holds the reader in thrall of the energy of scientific curiosity and ingenuity that may hold the key to solving our energy crisis -- or even send us to Mars.
Keywords: Nuclear energy -- Government policy -- History; Nuclear facilities -- History; Nuclear engineering -- History; Nuclear energy -- Government policy -- History; SCIENCE / Experiments & Projects; SCIENCE / History; SCIENCE / Physics / Nuclear; Nuclear energy -- Government policy; Nuclear engineering; Nuclear facilities